Challenges of Implementing Free and Open Source Software (FOSS): Evidence from the Indian Educational Setting - Thankachan, Briju; Moore, David (International Review of Research in Open and Distributed Learning, 2017)
The use of Free and Open Source Software (FOSS), a subset of Information and Communication Technology (ICT), can reduce the cost of purchasing software. Despite the benefit in the initial purchase price of software, deploying software requires total cost that goes beyond the initial purchase price. Total cost is a silent issue of FOSS and can only be evaluated in the particular environment in which it is adopted, in this case Kerala, India, fora state-level FOSS project called IT@School. This project is one of the largest deployments of free open source software FOSS-based ICT education in the world and impacts 6 million students and 200,000 teachers every year. This study analyzes the perception of 43 senior FOSS implementation project officials. It details how FOSS was introduced and reports on major challenges and how those challenges were overcome in a secondary educational setting in India. Email interviews, document analysis, and online case studies were used to collect the data. The lack of adequate resources to train the teachers was the single biggest challenge in the adoption of FOSS. The emerging strategies for efficient FOSS implementation could be used in other states in India and in other developing countries.